2017
DOI: 10.1136/emermed-2016-205998
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical simulation designed to evaluate the effect of telemedicine using Google Glass on cardiopulmonary resuscitation (CPR)

Abstract: Telematics support by an expert through GG improves success rates and completion times while performing CPR in simulated clinical situations for nurses in simulated scenarios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Recently, augmented reality glasses were shown to improve some aspects of performance during pediatric and adult code simulations. 93 These tools have not yet been evaluated for rapid response scenarios, nor have they been evaluated outside of simulated environments.…”
Section: Future Directionsmentioning
confidence: 99%
“…Recently, augmented reality glasses were shown to improve some aspects of performance during pediatric and adult code simulations. 93 These tools have not yet been evaluated for rapid response scenarios, nor have they been evaluated outside of simulated environments.…”
Section: Future Directionsmentioning
confidence: 99%
“…Supplemental Table 1 (http://links.lww.com/CCX/A858) summarizes the characteristics of the 17 articles that met inclusion criteria including year of publication, study type and setting, study design, equipment used, and primary outcome evaluated. The articles included five prospective trials (5–9), one prospective observational study (10), and 11 proof of technology demonstrations (11–21). The included studies were published as early as 2006 (17) to as recently as 2020 (18).…”
Section: Resultsmentioning
confidence: 99%
“…Twelve of the studies were conducted in a simulation environment (5, 6, 8, 9, 11–16, 18, 20) and five were performed in clinical environments (7, 10, 17, 19, 21). Only three of the 11 proof of technology demonstrations were performed in a clinical environment (17, 19, 21).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One randomized controlled trial found that the use of AR glasses in Pediatric Advanced Life Support (PALS) showed improved adherence to resuscitation guidelines, with a significant reduction of errors in defibrillation doses by 52.5%, compared to pocket reference cards [33]. Another controlled trial on CPR coaching using Google Glass showed a significant increase in the number of successful defibrillations by 32% [34]. While systematic reviews cannot validate the effects of such learning modules at this early stage [35], these promising results suggest an evolution in healthcare education with a potentially impactful influence on patient outcomes.…”
Section: Discussionmentioning
confidence: 99%